Conversational Maxim Violations in Satu Indonesia Talk Show Program on Net TV - Dewi Suhartini Sinaga; Sumarsih Sumarsih (Universitas Negeri Medan, 2016)
This study was aimed at examining the violations of conversational maxim in Satu Indonesia talk show. The objectives of this study were to examine the types of conversational maxim violations occurred in the talk show, to examine the realization of conversational maxim violations, and to elaborate the reasons. This study was conducted by descriptive qualitative method. The source of data was Satu Indonesia talk show. There were 44 episodes of Satu Indonesia talk show in 2014 which were consisted of 14 politics, 15 economics, and 15 socials. Then, the utterances of host and guests in 3 episodes of politics, 3 episodes of economics and 3 episodes of social were the data of this study. The technique of data collection was documentary technique and the instrument of data collection was recorder. The technique of data analysis was interactive model by Miles and Huberman. The findings showed that all conversational maxim violations. Quality maxim was dominantly violated in topic of politics; quantity maxim violation was dominantly violated in the topic of economics and social. Realizations of conversational maxim violations were realized through understatement, overstatement, contradiction, sarcasm, metaphor, associative clues, presupposition, personification, synecdoche, and analogy. Key Words: Conversational Maxim, Maxim Violations, Talk Show